(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This study attempted to investigate how cultural practices are shared on new media and whether this participation values cultural action or merely reviews it. For this purpose, it tested a sample of 270 posts from 6 pages of Algerian cultural associations on Facebook. Relying on the media survey approach and the content analysis tool, it concluded: A group of results, the most important of which were: that the associations shared cultural practices with their followers in both text and images most of the time, and primarily in the Arabic language. The followers interacted with these practices with admiration, commented on them positively, and shared them as well. As for the content of the publications through which practices were shared, most of it revolved around competitions, lectures, heritage, customs and traditions, tourist trips, and volunteer campaigns, and the social dimension dominated, followed by the economic and tourism dimension, then the scientific and academic dimensions of these contributions. Which carried the values of clinging to authenticity and heritage, solidarity and social solidarity, and the values of citizenship. Most of the time, the associations aimed to appear in the media and then to value and enhance cultural heritage. Those in charge of the associations and their supporters from local bodies and those interested in cultural affairs targeted the general public in the first place, without neglecting the educated public and the small public.